Estimation of diameter distributions for Pinus patula with the Weibull function - Pérez-López, Eloísa; Santiago-García, Wenceslao; Quiñonez-Barraza, Gerónimo; Rodríguez-Ortiz, Gerardo; Santiago-García, Elías; Ruiz-Aquino, Faustino (Instituto de Ecología, A.C., 2019)
The implicit prediction is an important tool to know the type of products that can be obtained from the forest in a given time, and thus to plan the sustainable forest management. In the Sierra Norte de Oaxaca, Mexico, there are even-aged stands of Pinus patula, a fast-growing timber species with economic and ecological value. The aim of this study was to estimate the growth and yield timber of this species with the diameter distribution models approach. The database consisted of 132 diameter distributions from 66 permanent sampling plots of 400 m2, located in Ixtlán de Juárez, Oaxaca, Mexico. Stand diameter distribution was estimated through Weibull function with parameters prediction and percentile prediction approaches. Also, minimum diameter and quadratic mean diameter projection models were fitted to recover the parameters and to estimate the diameter structure of stands on the future. The best system was the prediction of parameters because of this had the smaller bias in the prediction of the total volume with respect to an explicit projection system designed for the species. Therefore, it is recommended to use this implicit prediction system to plan the management of even-aged stands of P. patula.